PROFILEÂ INTEGRATED SCIENCE WORKSHEET BASED ON INQUIRY WITH THE THEMES â€œTHE INFLUENCE OF ADDICTIVE SUBSTANCES TO THE HUMAN EXCRETION SYSTEMâ€ IN CLASS IX JUNIOR HIGHT SCHOOL - EKO PUJIANTO, JEFRI (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Abstract. This research was intended to produce integrated science students’ worksheet inquiry based which was theoretically appropriate. This type of research is the development based on Kemp’s model development. In this research, the data collection method used was the students’ worksheet validation of inquiry to determine the feasibility of the theory, questionnaire to determine students' responses toward the students’ worksheets had been developed, the observation of the students’ activity during teaching and learning by using worksheets, and a test that was used to measure the indicators. The results of this research were integrated science students’ worksheet inquiry based by the theme